2021
DOI: 10.1108/ara-03-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Does managerial ability affect disclosure? Evidence from earnings press releases

Abstract: PurposePrior research shows that managers with lower ability release less accurate management earnings forecasts and have more earnings restatements, lower earnings persistence and lower quality accruals estimations. Yet, whether the impact of managerial ability (MA) on financial reporting can be extended to the narrative section of firms' financial disclosures needs to be theoretically and empirically examined. The authors theorize in this paper that managers with low ability opportunistically inflate the ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 103 publications
(197 reference statements)
1
22
0
1
Order By: Relevance
“…The findings in this study strengthen previous literature, stating that high-ability managers produce high earnings quality, less financial reporting fraud, and extensive disclosure (Baik et al, 2018(Baik et al, , 2020bDemerjian et al, 2013;García-Meca & García-Sánchez, 2018;Huang & Sun, 2017;Wang et al, 2017). The result of this study is also consistent with previous studies, which found that managerial ability could improve firms' reporting and disclosure (Baik et al, 2018), such as climate change disclosure (Daradkeh et al, 2022), corporate social responsibility (García-Sánchez et al, 2020), timeliness of financial disclosure (Abernathy et al, 2018), and disclosure quality (Yan et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The findings in this study strengthen previous literature, stating that high-ability managers produce high earnings quality, less financial reporting fraud, and extensive disclosure (Baik et al, 2018(Baik et al, , 2020bDemerjian et al, 2013;García-Meca & García-Sánchez, 2018;Huang & Sun, 2017;Wang et al, 2017). The result of this study is also consistent with previous studies, which found that managerial ability could improve firms' reporting and disclosure (Baik et al, 2018), such as climate change disclosure (Daradkeh et al, 2022), corporate social responsibility (García-Sánchez et al, 2020), timeliness of financial disclosure (Abernathy et al, 2018), and disclosure quality (Yan et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…High-ability managers also tend to produce more timely financial disclosures (Abernathy et al, 2018). Meanwhile, low-ability managers tend to inflate the disclosure (tone, numerical intensity, and readability) to positively influence the labor market's perceptions about their ability, which will cause a lower stock price reaction (Yan et al, 2021). Lowability managers are also willing to opportunistically manipulate the content of corporate disclosure to improve market perception and their reputation.…”
Section: Managerial Ability and Segment Disclosurementioning
confidence: 99%
See 1 more Smart Citation
“…This is shown through the results of previous studies, which found that CEOs with high managerial abilities could overcome two causes of inefficient investments, such as underinvestment and overinvestment (Gan, 2019). Furthermore the ability of the CEO matters because it could be associated with opportunistic behavior, because lower ability CEOs tend to release less accurate management earnings forecasts (Yan et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From a research perspective, it should be noted that most of the research conducted in the field of managerial ability, such as the research of Yan et al (2021); Bradley and Sun (2021); Chen and Chen (2020); Rashidi (2020) and Jabbarzadeh Kangarluie and Radi (2019), it has sought to quantitatively examine the relationship between this variable and other variables in the financial field, and less research has sought to link the relationship between quantitative and qualitative characteristics to the effect of managerial ability on protecting shareholders' interests to develop theories related to behavioral sciences in accounting from a practical point of view, it should be noted that in Iran, over time, along with improving the level of operational transparency, many efforts have been made to improve the performance of the company and managers against stakeholders, including the Corporate Governance Law of 2007; Publication of internal control report in 2012; Establishment of an audit committee in 2011 and, most importantly, the ranking of companies in terms of the quality of disclosure in 2014.…”
Section: Introductionmentioning
confidence: 99%